2001
DOI: 10.1108/eum0000000006229
|View full text |Cite
|
Sign up to set email alerts
|

Small firms under MICROSCOPE: international differences in production/operations management practices and performance

Abstract: Although the importance of operations in reaching world‐class competitiveness has been highlighted in the operations management literature, small and medium‐sized companies (SMEs) have been found to have a poor uptake of world‐class practices. Reports on a study of 285 SMEs located in Italy, the UK, and other northern European countries. The data are taken from the MICROSCOPE facilitated self‐assessment benchmarking database, which studied operations practices and performance in small firms. The level of worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 18 publications
12
124
0
10
Order By: Relevance
“…Eso sí, para evitar una posible falta de consistencia interna, los autores deciden emplear un único ítem para representar cada dimensión. De esta forma, la variable dependiente de la regresión multivariante, es decir el éxito competitivo, se presenta como una medida multidimensional compuesta de las percepciones que los gerentes de las pymes tienen sobre 7 de las dimensiones consideradas en trabajos de referencia (Pelham, 1997(Pelham, , 2000Camisón, 1999;Cagliano et al, 2001;Paige y Littrell, 2002): la cuota de mercado de su empresa, la productividad de la mano de obra, la solvencia, la reputación, la satisfacción de los clientes, la satisfacción de los empleados y la posición competitiva en términos de precio, calidad e innovación. Por otra parte, para no desvirtuar el análisis de los datos y evitar posibles problemas de interpretación de los resultados, se introdujeron en la regresión tres variables de control como determinantes del éxito competitivo: el tamaño, la antigüedad y el sector.…”
Section: Gráficounclassified
“…Eso sí, para evitar una posible falta de consistencia interna, los autores deciden emplear un único ítem para representar cada dimensión. De esta forma, la variable dependiente de la regresión multivariante, es decir el éxito competitivo, se presenta como una medida multidimensional compuesta de las percepciones que los gerentes de las pymes tienen sobre 7 de las dimensiones consideradas en trabajos de referencia (Pelham, 1997(Pelham, , 2000Camisón, 1999;Cagliano et al, 2001;Paige y Littrell, 2002): la cuota de mercado de su empresa, la productividad de la mano de obra, la solvencia, la reputación, la satisfacción de los clientes, la satisfacción de los empleados y la posición competitiva en términos de precio, calidad e innovación. Por otra parte, para no desvirtuar el análisis de los datos y evitar posibles problemas de interpretación de los resultados, se introdujeron en la regresión tres variables de control como determinantes del éxito competitivo: el tamaño, la antigüedad y el sector.…”
Section: Gráficounclassified
“…On the opposite side, several studies highlight a number of structural problems of SMEs that prevents them to gain remarkable results in some key operational performances, as delivery reliability and conformance quality (Cagliano and Spina, 2002). Cagliano et al (2001) have examined the adoption of world class practices by European SMEs. They found that firm size was linked to the difference in the use of practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have described decision categories in different contexts, such as product complexity (Spring and Dalrymple, 2000;Choudhari et al, 2012a;2012b) and process choice (Safizadeh and Ritzman, 1997;Olhager and Rudberg, 2002;Hill and Hill, 2009;Choudhari et al, 2012a;2012b). Some authors (Spring and Dalrymple, 2000;Cagliano et al, 2001;Choudhari et al, 2012a;2012b) have observed that company size (i.e., number of employees) influences decision categories. These factors have generally been used to understand how specific decision categories can be helpful in increasing performance and to explain how decision categories are related to internal and external contexts of the organisation (e.g., Raymond, 2005;Dìaz Garrido et al, 2007).…”
Section: Factors Influencing Decision Categoriesmentioning
confidence: 99%
“…Researchers and practitioners argue that, as subcontractors, small and medium-sized enterprises (SMEs) play a major role in the economy and in global supply chains (Thakkar et al, 2012;Hilmola et al, 2015). Previously, it was generally assumed that manufacturing practices were equally applicable to SMEs and large companies (Cagliano et al, 2001). However, research has shown that SMEs exhibit different characteristics to larger companies and are not simply small versions of the latter (Storey, 1994;Cagliano et al, 2001;Bridge et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation